Proceedings Electronic Components and Technology, 2005. ECTC '05.
DOI: 10.1109/ectc.2005.1441316
|View full text |Cite
|
Sign up to set email alerts
|

Chip-Package-Board Codesign of Highly Linear 3G-CDMA Upconverter Modules

Abstract: This paper presents a practical example of chip-packageboard codesign for a highly linear 3G-CDMA upconverter module. A 1.9 GHz upconverter MMIC is designed and implemented using InGaAs HBT foundry process. The goal for this MMIC design is to achieve the high linearity required in a W-CDMA system. In addition, the complete interconnect effects of package and PCB are considered rigorously by establishing their equivalent circuits with the help of the EDA EM-simulation tool. The proposed design for the upconvert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…It has been reported that the wirebond packages usually behave like low-pass filters to reduce the operating bandwidth of MMICs [15], [16], and also play important roles to move the input impedance away from the optimum point in noise-figure matching [17], [18] for a low-noise amplifier MMIC. In [19]- [21], we have studied the degradation of linearity due to the package and PCB for an upconverter MMIC. In this research, the package and PCB interconnects are also carefully modeled to account for their effects on the implemented direct-conversion IQ modulator MMIC during the on-board test.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the wirebond packages usually behave like low-pass filters to reduce the operating bandwidth of MMICs [15], [16], and also play important roles to move the input impedance away from the optimum point in noise-figure matching [17], [18] for a low-noise amplifier MMIC. In [19]- [21], we have studied the degradation of linearity due to the package and PCB for an upconverter MMIC. In this research, the package and PCB interconnects are also carefully modeled to account for their effects on the implemented direct-conversion IQ modulator MMIC during the on-board test.…”
Section: Introductionmentioning
confidence: 99%